2019
DOI: 10.1590/1983-21252019v32n102rc
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance and Biological Efficiency of Kale Intercropped With Spice Species

Abstract: Intercropping is a management strategy for the sustainability of agricultural systems, and is suitable for the production of vegetables. Kale is predominantly grown singly, but field observations have indicated that this crop has satisfactory productive potential when grown in intercrops with other vegetables. The objective of this work was to evaluate the agronomic performance and biological efficiency of kale plants intercropped with spice species. The experiment was carried out at the Didactic Horta of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…For the single arugula to have a yield equal to that of the intercropped systems in T2, T3 and T4, it would be necessary to increase the area cultivated as a single crop by 48%, 28% and 2% respectively. Hendges et al (2019), evaluating an intercrop of kale with the Apiaceae (coriander and parsley) used in this study and under similar growing conditions, found that crops of this family gave the highest values for the AEE, indicating greater biological efficiency. Apiaceae are known to be important crops when intercropped with other vegetables, where the better results seen under intercropped systems are due to crop diversification, which, in addition to agronomic benefits, allows a complement to marketing, affording greater financial returns (Sousa et al, 2018;Brito, 2018;Akshatha et al, 2019).…”
Section: Economic Indicatorsmentioning
confidence: 56%
See 2 more Smart Citations
“…For the single arugula to have a yield equal to that of the intercropped systems in T2, T3 and T4, it would be necessary to increase the area cultivated as a single crop by 48%, 28% and 2% respectively. Hendges et al (2019), evaluating an intercrop of kale with the Apiaceae (coriander and parsley) used in this study and under similar growing conditions, found that crops of this family gave the highest values for the AEE, indicating greater biological efficiency. Apiaceae are known to be important crops when intercropped with other vegetables, where the better results seen under intercropped systems are due to crop diversification, which, in addition to agronomic benefits, allows a complement to marketing, affording greater financial returns (Sousa et al, 2018;Brito, 2018;Akshatha et al, 2019).…”
Section: Economic Indicatorsmentioning
confidence: 56%
“…In this study, the highest value seen for the LER was in T2 (1.6), followed by T4 and T3 with values very close to 1.4 and 1.3 respectively. Hendges et al (2019), evaluating an intercrop of kale with the Apiaceae, coriander and parsley, also used in the intercrops grown in this study and under similar growing conditions, found that crops of this family afforded the highest values for LER, indicating greater biological efficiency. This result shows that the intercropped system favoured growth and production in the vegetables, which means that the combinations used were viable (Ribas et al, 2020).…”
Section: Biological Efficiency Of the Systemmentioning
confidence: 62%
See 1 more Smart Citation
“…Intercropping is a production system that aims to provide greater yields with less impact on the environment due to greater efficiency in the use of natural resources and inputs involved in the production process, bringing benefits to agricultural production of greater yields and better quality crops (Cecí lio Filho et al, 2015;Cecí lio Filho et al, 2017;Hendges et al, 2019;Wen et al, 2019;He et al, 2019;Barros Júnior et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that intercropping involves specific biological interactions and competitive relationships which can have a significant impact on crop performance and on the efficiency of the intercropping systems (Hendges et al, 2019;Nassary et al, 2020), studies to evaluate different species are of great importance, since they can define which species are the most productive when submitted to intercropping. Based on the above, the aim of this study was to evaluate the physiological aspects and effects on the competitive ability of arugula intercropped with different aromatic condiment species.…”
Section: Introductionmentioning
confidence: 99%